Stance in Media Reactions to the Declaration of 2023 Nigeria Presidential Election Winner - Onyinyechi Blessing Udoumoh (Linguistik Online)
The 2023 Nigerian presidential election was replete with expectations and optimism about the rebirth of a democratic government on the 25th of February, 2023. This has generated several online political discourses in Nigeria. The present study engages attitude; an aspect of Martin/ White’s (2005) Appraisal Framework to analyze the discursive features of the media reactions to the Independent National Electoral Commission (INEC), declaration of the 2023 Nigerian presidential election winner on Facebook. The research integrates both distant and close reading methods to study the data. The findings reveal that lexicons that align with the emotive state of the speakers and reveal the appraisal system of attitude, such as, affect, judgment, and appreciation predominate the discourse, with affect and judgment, deployed mostly to express negative emotions of unhappiness and retributions towards INEC for allegedly failing to conduct a free and fair election. The visualization of the study shows that the variegated responses of negative or positive affect and judgment expressed by Nigerians are indicative of the prevailing emotional surge of disappointment or excitement towards the conduct of the election and may be related to religious, tribal and ethnic sentiments.